Face Recognition using OpenCV - Duggi, Shivani; S, Khajabani; Harshitha, Katha; Shaguftha, NB; Nagaraj, M (International Journal of Computer Sciences and Engineering, 2020)
The rate of computer power steadily doubles every 13 months, with this face detection and recognition has transcended from an esoteric to a popular area of research in computer vision and one of the better and successful applications of image analysis and algorithm based understanding. Because of the intrinsic nature of the problem, computer vision is not only a computer science area of research, but also the object of neuro- scientific and psychological studies, mainly because of the general opinion that advances in computer image processing and understanding research will provide insights into how our brain works and vice-versa. Considering the general curiosity and interest in the matter, we propose to create and develop a facial recognition based attendance management system, using Intel’s open source computer vision project, OpenCV and Microsoft’s .NET framework. The paper describes how to take student’s attendance using face recognition. The face recognition is implemented with the help of Local Binary Patterns Histogram (LBPH) algorithm. The system will recognize the face of the student and saves the response in database automatically.